Contribution of Islamic Thought of Raja Ali Haji in the Development of the Malay Language to Become the Indonesian Language - Mansyur, Agus Salim; Hikmat, Mahi M; Marliana, Dina (Historia Madania: Jurnal Ilmu Sejarah, 2024)
This study aimed to actualize a historical figure who played a role as a hero, writers, and Muslim scholar through tracing Islamic stories and thought in his phenomenal works. He is Raja Ali Haji bin Raja Ahmad who was born in 1809 on Penyengat Island and died in the same place in 1872. The research methods used were the constructivist paradigm, subjective approach, and qualitative method. This was a type of historical study which implemented interview with informants, observation, library studies, and internet searching for data collection techniques. The actualization of Raja Ali Haji's Work is very important through social media platforms, so that the younger generation will know, understand, and realize the role of his contributions; Raja Ali Haji succeeded in popularizing the Malay language in various forms, so that it became the National Language and "World" Language; Many of Raja Ali Haji's works contain Islamic thoughts referring to the Al-Quran and Hadiths. One of the most phenomenal is the Gurindam 12 by teaching wisdom in life, guarding several parts of the human body, guarding the heart, and establishing friendship Keywords: Contribution, Actualization, History, Thought, Raja Ali Haji, Penyengat Island